1995
DOI: 10.1051/rnd:19950606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gonadotrophin deprivation on follicular growth in gilts

Abstract: Summary ― The endocrine and ovarian effects of hypophysectomy (n = 5) and gonadotrophin-releasing hormone (GnRH) antagonist administration (Antarelix) (n = 5) were studied in gilts by comparison with control animals (n = 6). All

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 22 publications
8
35
0
6
Order By: Relevance
“…There were no differences between the treatment groups with respect to ED and WEI, with one exception: primiparous sows treated with eCG tended to have shorter WEI values. This is consistent with the results of Engl [21] and Engl et al [20], and may occur because eCG exhibits both LH-and FSH-like activities [29]; LH stimulates the growth of follicles from 4 mm to preovulatory size [30], which in turn shortens the follicular phase and thus the WEI [31].…”
Section: Paritysupporting
confidence: 91%
“…There were no differences between the treatment groups with respect to ED and WEI, with one exception: primiparous sows treated with eCG tended to have shorter WEI values. This is consistent with the results of Engl [21] and Engl et al [20], and may occur because eCG exhibits both LH-and FSH-like activities [29]; LH stimulates the growth of follicles from 4 mm to preovulatory size [30], which in turn shortens the follicular phase and thus the WEI [31].…”
Section: Paritysupporting
confidence: 91%
“…The greater number of follicles could then respond better to PMSG (gonadotropin sharing both FSH and LH activity). Experiments of gonadotropin deprivation, using an administration of GnRH agonist or antagonist, have demonstrated that FSH and basal LH are necessary for follicular recruitment in sows (Driancourt et al, 1995;Brussow et al, 1996). It is believed (Quesnel et al, 1998) that changes in the ovulation rate may result from changes in the total number of growing follicles or in the rate of recruitment and/or selection.…”
Section: Discussionmentioning
confidence: 99%
“…The Antarelix dose (0.01 mg . kg -1 ) was the same as that used intravenously in gilts [4,11] and in goats [2] and subcutaneously in ewes [8]. For Cetrorelix the same dose was chosen arbitrarily.…”
Section: Treatmentsmentioning
confidence: 99%
“…In all the mares treated with Antarelix, LH secretion was strongly depressed during the 8 days of IV antagonist treatment, as in mares treated with ORG 30583 IM for 14 days during the follicular phase [28], in gilts treated with Antarelix IV for 4 or 7 days during the preovulatory period [4,11] and in macaques receiving Antarelix SC for 3 days during the preovulatory period [17]. In all mares, LH secretion began to be restored just after the end of the treatment and reached pre-treatment values 4.5 days after.…”
Section: Effects On Lh and Fshmentioning
confidence: 99%
See 1 more Smart Citation